(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
For better performance, efficient numerical methods describing physical behaviour of clothes are needed for any cloth simulation system. In this paper we report a quantitative research performed on the stability of the most widely used integration techniques in cloth simulation. Advantages and weaknesses of various integration techniques are listed for trade-off among stability, accuracy and speed. In this light, we offer a solution for choosing numerical methods when dealing with simulation problems.